Exploration of Language in Literary Works as a Means of Artistic Expression - Della Eka Putri (Institute of Multidisciplinary Research and Community Service, 2023)
Abstract: Literary works have an important role in expressing language. The language used in literary works can express the beauty and uniqueness of a culture. This paper discusses the exploration of language in literary works as a means of artistic expression. This research uses qualitative methods and literature study as data collection techniques. The results of the study show that literary works can be a means of expressing language. Language in literary works can give a deep and interesting impression. Literary works can also enrich the culture of a society by exploring language in their works.Keywords: language, literature, art, expression